2005
DOI: 10.1103/physrevlett.94.094302
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Flags Undergo Spontaneous Oscillations in Flowing Water

Abstract: By immersing a compliant yet self-supporting sheet into flowing water, we study a heavy, streamlined, and elastic body interacting with a fluid. We find that above a critical flow velocity a sheet aligned with the flow begins to flap with a Strouhal frequency consistent with animal locomotion. This transition is subcritical. Our results agree qualitatively with a simple fluid dynamical model that predicts linear instability at a critical flow speed. Both experiment and theory emphasize the importance of body i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
166
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 196 publications
(175 citation statements)
references
References 24 publications
(24 reference statements)
7
166
1
1
Order By: Relevance
“…This problem is somewhat reminiscent to that of the fluttering flag instability. The latter has been the focus of a large number of experimental ( [21]), computational ( [1,18]), and theoretical ( [2]) investigations. Of course, the flag is held stationary at one end in an incoming uniform flow field whereas the fish is freely moving.…”
Section: Introductionmentioning
confidence: 99%
“…This problem is somewhat reminiscent to that of the fluttering flag instability. The latter has been the focus of a large number of experimental ( [21]), computational ( [1,18]), and theoretical ( [2]) investigations. Of course, the flag is held stationary at one end in an incoming uniform flow field whereas the fish is freely moving.…”
Section: Introductionmentioning
confidence: 99%
“…The wake instability of a cylinder exists even when the cylinder is fixed. However, in the onset problem of a flag flapping, the study by Shelley, Vandenberghe, and Zhang 7 shows that the instability of a flag can be considered as a local phenomenon without considering the effect of vortex shedding. In the forced vibration of a cylinder, the cylinder is rigid.…”
Section: Introductionmentioning
confidence: 99%
“…Their experimental observations showed that an initiallystationaryfilamentstarteditsflappingmotionwhenbothitslengthandtheexternalflowspeed exceeded some threshold values. A further study by Shelley, Vandenberghe, and Zhang 7 showed that the instability of a flag also relied on the density ratio of the flag to fluid. They employed a temporal linear instability analysis to study the onset of the flag flapping.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations